PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP TEKANAN DARAH PADA PASIEN DENGAN HIPERTENSI DI PUSKESMAS BUNGURSARI - Rina Feradwiyanti; Wirdan Fauzi Rahman; Ruri Agis Melani (Jurnal Inovasi Penelitian, 2021)
Hypertension can be defined as high blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg (Wijaya, 2013). Factors that trigger Hypertension can be divided into two, namely those that cannot be controlled, such as family history, gender and age, while those that can be controlled are diet, smoking behavior, obesity and lack of physical activity (Cerika Rismayati, 2011). The design of this research is a Pre and Post Test Without Control Design with a quasi-experimental design. The Pre and Post Test Without Control design is used if the research only carries out intervention in one group without a comparison. The effectiveness of the treatment is assessed by comparing the post-test scores with the pre-test (Dharma Kelana Kusuma, 2015). The target population is the unit where a research result will be applied (generalized) (Dharma Kelana Kusuma, 2015). The target population in this study is hypertensive patients in Bungursari Village, Purwakarta in 2021. Based on research results and theory, researchers are of the opinion that hypertensive sufferers are very likely to experience vascular disorders which can cause differences in blood pressure measurement results between the left arm and the right arm. And it is best to measure blood pressure on both arms